The relationship between fetuin-A level and the clinical features of patients with coronary artery disease associated with iron deficiency - M. O. Konovalova; N. S. Mykhailovska (Zaporozhye State Medical University, 2023)
The aim of the study: to assess the relationship between the level of fetuin-A and features of clinical hemogram, ferrokinetic parameters, vegetative and structural-functional changes of the myocardium in patients with coronary artery disease (CAD) associated with different stages of iron deficiency (ID). Materials and methods. The study involved 90 patients with CAD: stable angina pectoris II-III FC (35 men and 55 women, age - 69 (61; 72)). All patients were divided into 4 clinical groups depending on the parameters of iron metabolism and hemogram: I (n = 16) - patients with absolute ID, II (n = 15) - with latent ID, III (n = 14) - with functional ID; IV (n = 45) - patients CAD without iron metabolism disorders. The physiological concentration of fetuin-A was determined in 15 conditionally healthy people. The results of echocardioscopy, Holter ECG monitoring and their relationship with the level of fetuin-A were analyzed. Results. In patients with CAD associated with various stages of ID, there is a decrease in the concentration of fetuin-A in direct proportion to the degree of progression of sideropenia was established. It was established that there is a relationship between the level of fetuin-A and the concentration of ferritin and transferrin saturation for patients with absolute ID as well as the number of erythrocytes in patients with functional ID. It was established that there is a relationship between the level of fetuin-A and PWd (rs = -0.60, p < 0.05) for patients with absolute ID; for patients with latent ID - with the E/A ratio (rs = +0.66, p < 0.05). In patients with absolute ID and latent ID a number of correlations between fetuin-A level and heart rate variability indicators in active and passive periods was established. The presence of a low level of fetuin-A in patients with CAD and ID increased the risk of left ventricular hypertrophy by 1.5 times, left ventricular diastolic dysfunction by 1.6 times, autonomic dysfunction by 2.14 times in the active period and 1.95 times in the passive period. Conclusions. In patients with CAD, there is a progressive decrease in the fetuin-A level depending on the degree of ID, which contributes to the deepening of disorders of iron metabolism and clinical hemogram, negatively affects the structural and functional state of the myocardium and heart rate variability, increases the risk of developing myocardial hypertrophy, left ventricular diastolic dysfunction and vegetative imbalance.